Spontaneously terminating ventricular fibrillation and asystole induced by silent ischaemia causing recurrent syncope. Issue 1 (1st July 1998) - Mustafa, M U A; Baker, C S R; Stephens, J D
Abstract : A 57 year old man was admitted for investigation of recurrent syncopal attacks. Holter monitoring during an attack while in hospital revealed a unique sequence of gross ST segment elevation, ventricular tachycardia, prolonged ventricular fibrillation, asystole, junctional and ventricular escape rhythm, and finally spontaneous restoration of sinus rhythm with severe ST segment depression. Subsequent coronary arteriography demonstrated severe stenoses of the right coronary artery, prompting percutaneous transluminal angioplasty and stenting. The patient has had no further syncopal attacks.